Assessment of two low-cost geological materials as adsorbents for arsenic - Coreño-Alonso, Oscar; González-Gómez, Leticia Elena; Coreño-Alonso, Juan (Tecnología y ciencias del agua, 2023)
Two easily accessible local materials, kaolin, and sediments from the reservoir of a dam, were evaluated to compare their efficiencies as adsorbents for As. The kaolin sample was composed mainly by kaolinite and quartz, while the sediments contained illite, montmorrillonite and quartz. Also, iron, calcium and magnesium minerals were present as minor components. The adsorption experiments were performed using batch equilibrium techniques. The samples were chemically treated using piranha solution, and trimesic acid, to study their effects on the adsorption capacity. The piranha treatment seems to be a good alternative to improve the adsorption capacity of kaolin. However, the intact reservoir sediments showed higher efficiencies than the intact or treated kaolin. On the other hand, the initial uptake of trimesic acid showed only a slightly positive effect on the arsenic uptake of the reservoir sediments. Most of the arsenic adsorption seems to be due to the finest particles of the sediments, composed mainly of iron minerals, while the organic matter contributes scarcely to the arsenic uptake. The influences of pH, contact time, initial arsenic concentration, and chemical treatments were studied. Freundlich and Dubinin-Kaganer-Radushkevich isotherm models were used to evaluate the arsenic uptake capacity of the intact and trimesic acid treated reservoir sediments. Maximum arsenic adsorption was completed almost within five hours of reaction, reaching a measured sorption capacity of 137 mg/kg for the intact sediments, slightly lower than for the trimesic treated sediments.